The ethnography of accounting, knowing and being : Malaysia, accounting research and the production of knowledge. - Mustafa, Hasri (Inderscience Publishers, 2009)
This paper reviews the major works in my recent doctoral dissertation 'Accounting, knowing and being' (Mustafa, 2006). The thesis includes three different empirical ethnographic settings that illustrate accounting differently, to contain the rational and objective view, the socio-political and monarchy view and the institutional and collective responsibility view. Prior to the revision, the paper briefly highlights the development of Malaysia since its inception in 1957. The paper argues 'Bumiputera', 'multiethnic society', 'UMNO', 'New Economic Policy', 'Islam' are the reality par excellence of Malaysia and they offer significant sights of accounting on both sides: the generality and specificity, the uniform and the contrasting and the simple and the complicated. The paper reproduces the core of Geertz's (1973) interpretive anthropology, namely: 'by isolating its elements', 'internal relationships' and 'in some general way' that were developed in the thesis. At the end of the revision, limitations of Institutional Theory are discussed, and research that commensurate with an appreciation of accounting to be seen as occupying a faculty of common sense is recalled. The paper underlines the concern of the thesis in enabling the application of research, which may be considered to be theoretical (in 'knowing'), to practice (in 'being').